The European Dimensionof the Ukrainian Constitution - Pankevych, Ivan; Kuchyk, Oleksandr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Nowadays the intensification of the processes of European integration of Ukraine sets a number of tasks of social, economic and political spheres for the authorities and institutions of civil society. In political and legal discourse, the discussion on the acquisition (achievement) of European standards by Ukraine for deepening the integration processes with the European Union and European regional institutes of multilateral sectoral cooperation is not ceased. Hence the urgent issue is Europeanity of public authorities functioning, governance and local self-government, as well as democratic values in the activities of institutions of civil society.
Keywords: integracja europejska; standardy europejskie; tożsamość; prawa człowieka; demokracja; praworządność; European integration; European standards; human rights; identity; rule of law; democracy